If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4+2c=2c-4
We move all terms to the left:
-4+2c-(2c-4)=0
We get rid of parentheses
2c-2c+4-4=0
We add all the numbers together, and all the variables
=0
c=0/1
c=0
| -3(1p+2)=-30 | | 6(6x+4)=3x-3 | | b2+5=8b-10 | | 4-10x=22 | | 21k-17=83 | | -10=n-2+3 | | 15=7+h+4 | | 8(5x-3)=6(-3x4) | | -6+9m=9m+3 | | 9/3x=-6/2 | | 10.58-12.3q=-13.9q-18.54 | | y2-2y-8=7 | | 45x+2=49x+58 | | -5h-17=19-14h | | 10d-9=-9d+10 | | 8y-40=180 | | 13m+2=18+14m | | 4(2a-1)=-10a-46 | | 5(6p+5)-2=-31+3p | | 2-25m-25=73 | | w2-15w+44=0 | | 3/4x-4=5/6 | | -8-2s=-2s+3 | | .25(20x+12)=-35 | | 10p-8=42 | | 3x+32=30x+5 | | (3)/(4)x-4=(5)/(6) | | g(-3)=2(-3)-5 | | 0.5p=p+0.5 | | 10q+6=6+10q | | 29=50-7y | | 1/2b-+9/4=7/4 |